The influence of R-Salbutamol on feedlot performance, carcass characteristics and meat quality in Dorper ram, wether and ewe lambs - Du Toit, Raoul (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2007.